2015
DOI: 10.1186/s40677-014-0008-z
|View full text |Cite
|
Sign up to set email alerts
|

The geotechnical characteristics of landslides on the sedimentary and metamorphic terrains of South-East Nigeria, West Africa

Abstract: Background: Landslides in Nigeria occur in various forms and vary in mode, scale and frequency. The variations appear to be significantly controlled by geologic setting, hence the need to study in detail the distinctive features that differentiate landslides in sedimentary environments from those on metamorphic localities. The aim is to understand the actual features impacted on the landslides by geology, from which future predictions of occurrence and identification of instability could be based. The recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…According DIBI data 2019 [2], there were 512 landslides that occurred in Indonesia. Landslide event usually occurs during the peak of wet season and in the hilly area [3]. The threat of landslides is currently getting higher by the rising population whose lives are at stake as they live on the slopes inhilly area.…”
Section: Introductionmentioning
confidence: 99%
“…According DIBI data 2019 [2], there were 512 landslides that occurred in Indonesia. Landslide event usually occurs during the peak of wet season and in the hilly area [3]. The threat of landslides is currently getting higher by the rising population whose lives are at stake as they live on the slopes inhilly area.…”
Section: Introductionmentioning
confidence: 99%
“…Igwe [27] also reported that positive correlation exist between frequency of landslide and slope angle, but however noted that landslides occur more on slopes with angles greater than 30° but less than 40°. Thus slope geometry could be one of the causes of the shallow sliding on the slope surfaces shown in Fig.…”
Section: Dump Slope Physical Attributementioning
confidence: 99%
“…Result from principal component analysis suggested that combination of height and width (dimensions) as factors of slope failure are more significant on the stability of slopes in Enyigba mine dumps than slope angles (inclinations), and therefore implies that slope height and width could be key determinants of slope failure in the area. Also, results of the PCA and Pearson's correlation signifies that there could be many factors that causes slope instability or decrease in shear strength of slope materials [43], but some factors could be more prominent depending on the area [27].…”
Section: Dump Slope Physical Attributementioning
confidence: 99%
See 1 more Smart Citation
“…In many regions of the world, the impacts of landslides have been cataclysmic with damages worth several millions of dollars in monetary losses, and are responsible for thousands of deaths and injuries annually. Regularly, they cause long-term economic disruption, population displacement, and negative effects on the natural environment, (Ancuţa et al 2007;Highland and Bobrowsky 2008;Igwe, 2015). Though landslides can occur in different parts of the world, their mechanisms, impacts and management is often determined by the geology, hydrogeology and geomorphology of the area.…”
Section: Introductionmentioning
confidence: 99%